Quality of life and depression among metastatic breast cancer patients - Slovacek, Ladislav; Slovackova, Birgita; Slanska, Iva; Petera, Jiri; Priester, Peter (Medical oncology (Northwood, London, England), 2010)
Depression is seen in many cancer patients. It is common in the general population and in adults and children with cancer and frequently coexists with anxiety and pain. The pilot study evaluated the level of the global quality of life (QoL) and the incidence and the relevance of the depression among metastatic breast cancer patients in a programme of palliative cancer care. The study is prospective and cross-sectional. Dates were obtained during year 2008 among 41 patients. The mean age of all 41 subjects was 58 years old (aged 41-80 years old). The Czech version of Zung self-rating depression scale was performed for the evaluation of the depression. The Czech version of generic European Quality of Life Questionnaire EQ-5D was performed for the evaluation of the level of global QoL. The statistical evaluation presents that mean ZSDS (Zung self-rating depression score) certifies the presence of the signs of the moderate depression among metastatic breast cancer patients (ZSDS range was 60-69). The incidence of the depression was 61% (25 of all 41 subjects). The relevance of the depression is characterized: the severe depression was proved in five of all 25 subjects, the moderate depression in 10 of all 25 subjects, and the mild depression in 10 of all 25 subjects. The global QoL among metastatic breast cancer patients is on very low level. The mean EQ-5D score (dimension of QoL) was 55%. The mean EQ-5D VAS (subjective health status) was 59.2%. The results showed that subsist association between metastatic breast cancer, depression, and the low level of the global QoL.
Keywords: dospělí; metastázy nádorů; nádory prsu; Palliative Care; průzkumy a dotazníky; Female; paliativní péče; Quality of Life; Adult; ženské pohlaví; průřezové studie; Surveys and Questionnaires; kvalita života; lidé; Pilot Projects; Breast Neoplasms; pilotní projekty; Aged, 80 and over; prospektivní studie; Cross-Sectional Studies; depresivní poruchy; Aged; Czech Republic; Prospective Studies; Depressive Disorder; Česká republika; lidé středního věku; deprese; senioři nad 80 let; senioři; Neoplasm Metastasis; Depression; Middle Aged; Humans